Development of Android-Based 3d Animation Learning Applications to Support Distance Learning for the D4 Animation Study Program, Udinus Semarang - Nur Rokhman; Novi Hendriyanto (Journal of Applied Intelligent System, 2022)
The existence of the COVID-19 pandemic has become a big problem in practicum courses, especially the 3D1 Animation course at the Dian Nuswantoro University animation study program, Semarang. Lecturers cannot guide students directly when experiencing obstacles in the learning process such as during face-to-face learning. The purpose of this research is to create an android application for learning media 3d1 animation. In this application there are several menus including the semester learning plan menu, video tutorials, task collection, consultation with lecturers, remote desktop requests and othersRemote desktop features to make it easier for lecturers to guide students remotely. This study uses the waterfall method, namely software requirements analysis, design, development, testing, and maintenance with testing using the black box method. The test results show that each aspect has results that can be concluded as successful and feasible. This research succeeded in developing android-based 3d1 animation learning media.